Assessment of the Prevalence and Patterns of Violence against Healthcare Workers in Nigeria: A Multicentre Study - Alphonsus Rukevwe Isara; Zara William Wudiri; Hadiza Abigail Agbo; Luret Albert Lar; Adesuwa Queen Aigbokhaode; Nyemike Simeon Awunor; For Association of Public Health Physicians of Nigeria (Nigerian Postgraduate Medical Journal)
Background: In Nigeria, violence against healthcare has adversely affected the access to and delivery of healthcare services with serious consequences for healthcare workers (HCWs). This study assessed the prevalence and patterns of violence against HCWs in areas of armed conflict, areas of other situation of violence and areas not affected by conflict in Nigeria. Methodology: A cross-sectional study utilising a mixed method approach comprising both quantitative survey and qualitative data collection methods. All the categories of HCWs in public healthcare facilities participated in the study. Ethical approval for this study was obtained from the respective Health and Research Ethics Committees of the respective study sites. Results: A total of 1,218 HCWs comprising Borno State, 407 (33.4%), Plateau State, 401 (32.9%) and the Federal Capital Territory 410 (43.7%) were interviewed. The overall prevalence of physical and psychological violence was 16.7% and 62.4%, respectively. Pushing and slapping were the predominant forms of physical violence. Weaponized violence with weapon was the highest in conflict areas. Verbal abuse, threats, bullying and harassment were the predominant forms of psychological violence. The major consequences of violent attacks on the HCWs were lack of job satisfaction, loss of confidence, low self-esteem, decreased productivity and post-traumatic stress disorder. Conclusions: The overall prevalence of violent attacks on HCWs was high. The perpetrators of violent attacks were mainly patient relatives and patients/clients. The factors predisposing to violent attacks were patients-related issues, service delivery, working conditions of the hospitals, expectations of patient relatives and impatience of hospital staff.